FORMULASI ACNE GEL EKSTRAK KAYU SECANG (Caesalpinia sappan L) DENGAN HPMC SEBAGAI GELLING AGENT - Yulyuswarni Yulyuswarni (Jurnal Analis Farmasi, 2019)
FORMULATION OF ACNE GEL SAPPAN WOOD EXTRACT (Caesalpinia sappan L) WITH HPMC AS GELLING AGENT Acne (acne vulgaris) is an abnormal condition of the skin due to the production of excess oil glands which causes blockage of the skin pores. These troublesome skin conditions can cause significant physiological problems such as the crisis of self-confidence. Acne develops into inflammation (inflammatory acne) when infected with bacteria, especially the bacteria Propioni bacterium acnes.Secang wood (Caesalpinia Sappan L) is one of the potential plants as anti-bacterial, anti-inflammatory, antihistamine, and anti-oxidant which has been widely used by the people of Indonesia. This study aimed to obtain a formulation of acne gel secang wood extract (Caesalpinia sappan L) at a concentration of 1% and on the basis of HPMC (Hydroxypropyl Methylcellulosa) as a gelling agent at concentrations of 3%, 4%, and 5% that met organoleptic requirements, homogeneity, pH and spreadability. Acne Gel of Sappan wood (Caesalpinia sappan L) with HPMC as gelling agent have a yellowish-red color, semi-solid texture, homogeneous, pH range 4.6-5.1, spreadability that meets the requirements of 6.3 cm. The formula for acne gel that fulfills the requirements is formula 1 with 3% HPMC concentration.Keywords : Gel, secang wood extract, HPMCJerawat (acne vulgaris) adalah kondisi abnormal kulit akibat produksi kelenjar minyak berlebih yang menyebabkan penyumbatan pori-pori kulit. Kondisi kulit yang menyusahkan ini dapat menyebabkan masalah fisiologis yang signifikan seperti krisis kepercayaan diri. Jerawat berkembang menjadi inflamasi(inflammatory acne) apabila terinfeksi bakteri, terutama bakteri Propioni bacterium acnes. Kayu Secang (Caesalpinia Sappan L) merupakan salah satu tanaman yang potensial sebagai anti bakteri, anti inflmasi, antihistamin, dan anti oksidan yang sudah banyak di gunakan oleh masyarakat Indonesia. Penelitian ini bertujuan untuk mendapatkan formulasi sediaan acne gel ekstrak kayu secang (Caesalpinia sappan L) pada konsentrasi 1% dandengan basis HPMC (Hydroxypropyl Methylcellulosa) sebagai gelling agent pada konsentrasi 3%, 4%, dan 5% yang memenuhi syarat organoleptik, homogenitas, pH, dan daya sebar. Sediaan acne gel ekstrak kayu Secang (Caesalpinia sappan L) dengan HPMC sebagai gelling agent memiliki warna merah coklat kekuningan, tekstur setengah padat, homogen, range pH 4.6-5.1, daya sebar yang memenuhi syarat 6.3 cm. Formula acne gel yang memenuhi syarat adalah formula 1 dengan konsentrasi HPMC 3%.Kata Kunci : Gel, Ekstrak Kayu Secang, HPMC